Neutralization of Human Cytomegalovirus by Human CD13-Specific Antibodies - Giugni, Terrence D. (J Infect Dis, 1996)
The mechanisms of inhibition of cytomegalovirus (CMV) infection by human CD13 (aminopeptidase N)-specific antibodies were studied. These antibodies protect CD13-negative and -positive cells from CMV infection only if incubated with the virus inoculum, suggesting they bind to CMV virions. The association of a CD13-like molecule with virions was further supported by the transfer of CD13 immunoreactivity to the surface of CD13-negative cells upon binding of CMV; the binding of CD13-specific antibodies directly to the surface of CMV virions; and the presence of anti-CD13 immunoreactive bands, including one with mobility similar to that of native cellular CD13 on immunoblots of proteins of purified CMV particles. Importantly, CD13-specific antibodies neutralize CMV in urine of neonates with congenital CMV, indicating that the CD13-like molecule is associated with natural CMV and not acquired in vitro. These studies demonstrate that a CD13-like molecule is associated with CMV particles and may be important in CMV pathogenesis.